Catalysing financial inclusion in South Africa's rural landscape: a theoretical discourse of PoS business model - Iwara, Ishmael Obaeko (Penerbit Universiti Kebangsaan Malaysia, 2024)
In countries like South Africa, where cash plays a pivotal role in social and economic life, limited access to financial institutions, in rural areas has led to significant economic challenges for citizens and businesses. This limitation has further exacerbated the financial exclusion of the underserved population resonating with poor economic growth. In addressing the issue, this desktop-based theoretical discourse, draws on the Technology Acceptance Model, Schumpeterian Entrepreneurship Theory, and Circular Flow of Income Model to conceptualise cash point-of-sale business model, as an innovative mechanism with the potential to spearhead the country’s financial inclusion efforts, entrepreneurial imperatives and local economic participation. The findings provide valuable insights for policymakers and financial institutions to design and implement effective financial inclusion policies in rural areas. By addressing unique challenges faced by rural communities, such as limited infrastructure and lower levels of education, a more inclusive and resilient financial ecosystem can be achieved, contributing to broader social and economic development goals in South Africa's rural landscape. An exploratory empirical study is further recommended to pave the way for the development of a contextual framework to guide the model’s implementation in South Africa.